2015
DOI: 10.3892/mmr.2015.4652
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt signaling pathway is involved in the neurotrophic effect of senegenin

Abstract: Neurodegenerative diseases are frequently associated with the loss of synapses and neurons. Senegenin, extracted from the Chinese herb Polygala tenuifolia Willd, was previously found to promote neurite outgrowth and neuronal survival in primary cultured rat cortical neurons. The aim of the present study was to investigate the underlying mechanisms of senegenin-induced neurotrophic effects on rat cortical neurons. Primary cortical rat neurons were treated with various pharmacological antagonists and with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Notably, Sen could increasing the phosphorylation of PI3K and Akt, which was consistent with the previous study. 64 Therefore, Sen may reduce apoptosis by regulating the expression of Bcl-2 family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Sen could increasing the phosphorylation of PI3K and Akt, which was consistent with the previous study. 64 Therefore, Sen may reduce apoptosis by regulating the expression of Bcl-2 family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that the effects may be related to stimulating different upstream pathways of CREB via the MAPK/ERK1/2, phosphoinositide-3 kinase (PI3K), and CREB-BDNF pathways, which was demonstrated in vitro (19). The neurotrophic effects of senegenin were significantly inhibited by the A 2A receptor antagonist ZM241385 and the specific PI3K inhibitor LY294002, suggesting that senegenin may be involved in the PI3K/Akt signaling pathway (50,59).…”
Section: Neuroprotective Mechanisms Neuronal Synaptic Plasticity and Proliferationmentioning
confidence: 98%
“…DISS and tenuifoliside (A, B, and C), two natural oligosaccharide esters from P. tenuifolia roots, improved neuronal synaptic plasticity, promoted nerve cell proliferation, and showed neuroprotective effects via inhibiting glucocorticoid-induced NOS hyper-activation, upregulating the phosphorylation of CREB, and increasing the expression of BDNF in corticosterone-induced SH-SY5Y cells (19). Senegenin was also found to promote neurite outgrowth and neuronal survival in primary cultured rat cortical neurons (50,59). The studies showed that the effects may be related to stimulating different upstream pathways of CREB via the MAPK/ERK1/2, phosphoinositide-3 kinase (PI3K), and CREB-BDNF pathways, which was demonstrated in vitro (19).…”
Section: Neuroprotective Mechanisms Neuronal Synaptic Plasticity and Proliferationmentioning
confidence: 99%
“…At a dose of 5 lg/mL, senegenin promoted neuritogenesis with a notable increase in the number of neurites, mean length, and maximum length by up-regulating MAP2 and Gap-43 expression or inhibition of ASK1 and JNK signalling pathways (Jesky and Chen 2016). Another research suggests that senegenin exerts neuroprotective effects may be associated with the PI3K/Akt signalling pathway (Pi et al 2016). In addition, P. tenuifolia extract can also promote the nerve growth factor release in astroglial cells (Yabe et al 2003).…”
Section: Promote Neuronal Proliferationmentioning
confidence: 99%